THE EFFECTIVENESS OF INVITATION INTO INQUIRY MODEL TO STUDENTS’ CRITICAL THINKING SKILLS IN DIFFRACTION GRATING MATERIAL - Setiawan, Puji Agus; Nugroho, Sunyoto Eko; Marwoto, Putut (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
It is a fact that physics is related to the application of physic formulas and mathematic approach. Invitation into inquiry is a learning model which emphasizes on the solution of daily problem. This research aims to unveil the influence of invitation into inquiry model to students’ critical thinking skills. In this research, the researcher employed mixed methods design by combining quantitative and qualitative approaches. The subject of the research is the XII grade students of SMA Negeri 2 Blora, academic year 2017/2018. The collection of the data were in the sequence of observation, tests, interview, and questionnaire. The result of the research found that the t-test obtained the significance of 0.02 or t_count<t_table. The most influencing indicator of critical thinking is in the ability of making hypothesis where it had the biggest gap of N-gain. The conclusion of this research showed that the model of invitation into inquiry had positive influence to students’ critical thinking skills.